PENGGUNAAN ARTIFICIAL INTELLIGENCE UNTUK EVALUASI KINERJA DAN PENGEMBANGAN KETERAMPILAN KARYAWAN SECARA REAL-TIME - Elma Kumala; Muhshonatun Nandhiroh; O'ol Prasetyo; Ifa Khoiria Ningrum (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
The rapid development of digital technology has encouraged organizations to adopt Artificial Intelligence (AI) to improve the effectiveness of performance evaluation and employee skill development. Conventional evaluation systems, which are typically periodic, are considered less capable of providing timely and relevant feedback. Therefore, AI emerges as a solution through its ability to analy ze data in real-time, objectively, and continuously. This study employs a descriptive qualitative approach using a library research method, drawing on scientific journals and credible publications. Data analysis is conducted using content analysis techniques by comparing traditional evaluation systems with AI-based systems. The results show that AI can improve the accuracy of skill mapping by up to 80% and increase the speed of problem detection by up to 150% compared to manual methods. AI also enables the personalization of training programs based on individual needs, thereby enhancing the efficiency and effectiveness of human resource development. In addition, instant feedback generated by AI has been proven to increase employee motivation and productivity. However, the effectiveness of AI largely depends on data quality, system transparency, and integration with human roles. With proper management, AI has the potential to become a strategic tool in supporting improved performance and organizational competitiveness.